2017
DOI: 10.1002/ajmg.a.38064
|View full text |Cite
|
Sign up to set email alerts
|

Additional three patients with Smith‐McCort dysplasia due to novel RAB33B mutations

Abstract: Smith-McCort dysplasia (SMC OMIM 615222) and Dyggve-Melchior-Clausen dysplasia (DMC OMIM 223800) are allelic skeletal dysplasias caused by homozygous or compound heterozygous mutations in DYM (OMIM 607461). Both disorders share the same skeletal phenotypes characterized by spondylo-epi-metaphyseal dysplasia with distinctive lacy ilia. The difference rests on the presence or absence of intellectual disability, that is, intellectual disability in DMC and normal cognition in SMC. However, genetic heterogeneity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Recent studies reported mutations of RAB33B in human patients with Smith–McCort dysplasia 2325 . Smith-McCort dysplasia is a skeletal dysplasia characterized by a short neck and short trunk dwarfism with a barrel-shaped chest and rhizomelic limb shortening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported mutations of RAB33B in human patients with Smith–McCort dysplasia 2325 . Smith-McCort dysplasia is a skeletal dysplasia characterized by a short neck and short trunk dwarfism with a barrel-shaped chest and rhizomelic limb shortening.…”
Section: Discussionmentioning
confidence: 99%
“…Rab33b interacts with Golgi proteins such as GM130, rabaptin-5 and rabex-5 21 , and modulates autophagosome formation by interacting with Atg16L 22 . In addition, mutations in human RAB33B are found in patients with an autosomal recessive skeletal dysplasia, Smith–McCort dysplasia 2325 . In zebrafish, three rab33 genes, rab33a , rab33ba and rab33bb , have been identified 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Rab39B, a neuronal-specific protein, is a novel Rab GTPase that localizes to the Golgi and is related to synapse formation. Mutations in the Rab33B coding gene cause Smith-McCort dysplasia (121) and mutations in the Rab39B gene cause X-linked mental retardation (122).…”
Section: Mutant Golgi Resident Proteins Involved In Diseasementioning
confidence: 99%
“…Mutations in RAB33B have been associated with a rare autosomal recessive spondylo-epi-metaphyseal disorder, SMC [98,99,100]. Patients with SMC present skeletal deformities consisting of marked short stature, barrel-shaped chest, disproportional length of the proximal limb, a combination of both outward and lateral curvature of the spine and small pelvis with slipped capital femoral epiphysis [101].…”
Section: Disease and Future Perspectivesmentioning
confidence: 99%